Pendampingan Penyusunan Business Plan dan Penguatan Kelayakan Usaha Untuk Meningkatkan Akses Pembiayaan UMKM Di Desa Jimbaran Wetan, Sidoarjo - Mutiara Rachma Ardhiani; Sugijanto; Ferry Hariawan; Fachrudy Asj’ari; Christina Menuk Sri Handayani (Ekobis Abdimas, 2026)
Limitations in developing business plans and a lack of understanding of business feasibility are among the main obstacles faced by Micro, Small, and Medium Enterprises (MSMEs) in accessing financing. This situation is also found among MSMEs in Jimbaran Wetan Village, Sidoarjo, where the majority of them still operate without a structured business plan. This community service activity aims to increase the capacity of MSMEs through mentoring in business plan development and strengthening business feasibility to expand access to financing. The implementation method is three-stage: preparation, implementation, and evaluation, using a participatory training and mentoring approach. The results of the activity indicate an increase in participants' understanding and skills in developing systematic business plans, as well as their ability to assess business feasibility more rationally. Furthermore, participants are also beginning to develop business proposals that better align with the requirements of financial institutions. Thus, this activity makes a significant contribution to improving MSME readiness to access financing sources and supporting business sustainability.